THE IMPLICATIONS OF CRYPTOCURRENCY AND BLOCKCHAIN ON ACCOUNTING SYSTEMS: A CONTEMPORARY LITERATURE REVIEW - Siti Intan Nurdiana Wong Abdullah (Count : Journal of Accounting, Business and Management, 2025)
This study aims to explore the implications of cryptocurrency and blockchain technology on accounting systems, focusing on how these digital innovations are reshaping financial reporting, auditing, and regulatory frameworks. Using a qualitative library research approach, the study conducted a systematic literature review of scholarly articles, professional reports, and regulatory publications published between 2019 and 2023. The analysis revealed three major findings: (1) inconsistent accounting treatments of crypto-assets across jurisdictions; (2) limited integration of blockchain in traditional accounting systems due to technical and organizational barriers; and (3) a growing digital skills gap among accounting professionals. The novelty of this research lies in its interdisciplinary synthesis of regulatory, technological, and educational perspectives, which are often treated separately in previous studies. Additionally, it offers a comparative lens across emerging and developed economies to better understand policy fragmentation. Unlike earlier research that primarily highlights the theoretical potential of blockchain, this study emphasizes the practical, ethical, and institutional challenges of implementation. The findings contribute to the global accounting discourse by identifying urgent needs for regulatory harmonization, curriculum reform, and upskilling initiatives. In conclusion, the study provides a timely and comprehensive view of how the accounting profession must evolve to remain relevant and reliable in the era of digital finance. Its implications are vital for standard setters, educators, practitioners, and policymakers navigating the rapid transformation of accounting in the digital age.